Prediction of cerebral hemorrhagic supratentorial stroke acute period outcome on the basis of the assessment of secondary intraventricular hemorrhage severity in the onset of the disease - A. A. Kuznietsov (Zaporozhye State Medical University, 2017)
Criteria for a short-term vital and functional prognosis for cerebral hemorrhagic supratentorial stroke (CHSS) acute period, that would take into account the secondary IVH severity in the onset of the disease, are currently lacking. The main purpose of the study was to develop criteria for the prediction of cerebral hemorrhagic supratentorial stroke acute period outcome on the basis of the assessment of secondary intraventricular hemorrhage (IVH) severity in the onset of the disease. Materials and methods. A complex clinical and paraclinical study was conducted in 70 patients (38 men and 32 women, aged 66 (58; 74) years) who have CHSS and secondary IVH confirmed by a clinical and neuroimaging examination, who were hospitalized within the first 24 hours since the onset of the disease and received conservative therapy. Intraventricular hemorrhage (IVH) severity was assessed in terms of Graeb Scale, IVH Scale and LeRoux Scale. To determine the prediction criteria, ROC analysis was used, calculating sensitivity (Se) and specificity (Sp) parameters. Results. Lethal outcome was registered in 18.6 % cases, unfavorable functional outcome (modified Rankin Scale score (mRS) = 4-5 on the 21st day of the disease) - in 44.3 % patients. It was determined that IVH Scale (AUC=0.94, P < 0.05) has a higher informative value than Graeb Scale (AUC = 0.89, P ˂ 0.05) and LeRoux Scale (AUC = 0.88, P ˂ 0.05) for a lethal prognosis of CHSS acute period outcome. It was detected that Graeb Scale, Intraventicular Hemorrhage Scale and LeRoux Scale are more informative for the determination of vital rather than functional prognosis of CHSS acute period outcome (AUC = 0.89 versus AUC = 0.74 for Graeb Scale, P < 0.05; AUC = 0.94 versus AUC = 0.79 for IVH Scale, P < 0.05; AUC = 0.88 versus AUC = 0.72 for LeRoux Scale, P < 0.05). Conclusions. Predictors of the lethal outcome of CHSS acute period are Graeb Scale score ˃5 (Se = 84.6 %, Sp = 77.2 %), IVH Scale score ˃16 (Se = 84.6 %, Sp = 96.5 %) and LeRoux Scale score ˃9 (Se = 84.6 %, Sp = 86.0 %). Graeb Scale score ≤3 (Se = 69.2 %, Sp = 72.7 %), IVH Scale score ˂8 (Se = 69.2 %, Sp = 79.5 %) and LeRoux Scale score ≤3 Se = 69.2 %, Sp = 72.7 %) are the criteria for the favourable functional outcome of CHSS acute period (mRS score ≤3 on the 21st day).